Unconfined compression properties of a porous poly(vinyl alcohol)-chitosan-based hydrogel after hydration - Lee, S.Y.; Pereira, B.P.; Yusof, N.; Selvaratnam, L.; Yu, Z.; Abbas, A.A.; Kamarul, Tunku (Elsevier, 2009)
A poly(vinyl alcohol) (PVA) hydrogel composite scaffold containing N,O-carboxymethylated chitosan (NOCC) was tested to assess its potential as a scaffold for cartilage tissue engineering in a weight-bearing environment. The mechanical properties under unconfined compression for different hydration periods were investigated. The effect of supplementing PVA with NOCC (20 wt. PVA:5 vol. NOCC) produced a porosity of 43.3, and this was compared against a non-porous PVA hydrogel (20 g PVA: 100 ml of water, control). Under non-hydrated conditions, the porous PVA-NOCC hydrogel behaved in a similar way to the control non-porous PVA hydrogel, with similar non-linear stress-strain response under unconfined compression (0-30 strain). After 7 days' hydration, the porous hydrogel demonstrated a reduced stiffness (0.002 kPa, at 25) strain), resulting in a more linear stiffness relationship over a range of 0-30 strain. Poisson's ratio for the hydrated non-porous and porous hydrogels ranged between 0.73 and 1.18, and 0.76 and 1.33, respectively, suggesting a greater fluid flow when loaded. The stress relaxation function for the porous hydrogel was affected by the hydration period (from 0 to 600 s); however the percentage stress relaxation regained by about 95, after 1200 s for all hydration periods assessed. No significant differences were found between the different hydration periods between the porous hydrogels and control. The calculated aggregate modulus, H(A), for the porous hydrogel reduced drastically from 10.99 kPa in its non-hydrated state to about 0.001 kPa after 7 days' hydration, with the calculated shear modulus reducing from 30.92 to 0.14 kPa, respectively. The porous PVA-NOCC hydrogel conformed to a biphasic, viscoelastic model, which has the desired properties required for any scaffold in cartilage tissue engineering. (C) 2009 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.